The Museum and the 44-day Artsakh War - Muradyan, Haykuhi; Yeranyan, Nzhdeh (History and Culture, 2023)
The article presents the issues of preservation of Artsakh's cultural heritage, in particular the issues of museum activities, their preservation and protection during and after the Artsakh 44-day war. Especially those museums and collections that came under Azerbaijani control as a result of the 44-day war were examined.As a result of the war, one of the most damaged areas in the cultural life of Artsakh is the museum. As a result of the war, 17 state and private museums and collections remained in the territories occupied by the armed forces of Azerbaijan. The museums which collection was able to be evacuated from the occupied territories faced serious problems. These problems are especially related to the preservation and publicization of cultural values: where should these museum collections be kept, according to what principle and context should they be presented to international community, how should they be presented to the public, the problem of being cut off from one's own community also becomes relevant. The research is based on in-depth interviews with museum directors, employees, museums, the Ministry of Education and Culture of Artsakh, as well as on the study of videos shared by different Azerbaijani users on various Internet platforms (Tik Tok, Twitter, Facebook, YouTube, Telegram).The research was carried out within the framework of the "Monument Watch" project.
Keywords: Museum; war; private collection; heritage in crisis; occupied territory; "saved" and "lost" museums